Metalcutting fluids - Rembiesa, David; Goodin, Kate (Fundamental manufacturing processes)
An examination of the functions that fluids provide during the cutting process, types of fluids, applications, maintenance, and safety requirements. Also illustrates newer technologies such as minimum quantity lubrication and dry machining.